PENINGKATAN KETERAMPILAN MENULIS TEKS WAWANCARA MELALUI MODEL PROBLEM BASED LEARNING DENGAN MEDIA KARTU PADA MURID KELAS IV SD NEGERI 1 PASEBAN TAHUN AJARAN 2025/2026 - Rosidi, Sholeh; Dwi Bambang Putut Setiyadi; Agus Yuliantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of the Problem Based Learning (PBL) model assisted by card media and to improve the interview text writing skills of fourth-grade students at SD Negeri 1 Paseban in the 2025/2026 academic year. The study employed a Classroom Action Research (CAR) approach using a spiral design consisting of planning, action, observation, and reflection in each cycle. The research subjects consisted of 22 students. Data were collected through observation, tests, and documentation. The data were analyzed qualitatively and quantitatively using descriptive analysis. The results showed that the implementation of the Problem Based Learning (PBL) model assisted by card media was able to improve students’ learning activities, teachers’ teaching skills, and students’ achievement in writing interview texts. Students became more active in discussions, asking questions, expressing opinions, and conducting direct interview practices. Teachers’ teaching skills also improved through the use of more varied, interactive, and contextual learning methods and media. Students’ learning outcomes improved in each cycle until classical learning mastery was achieved. Learning through the Problem Based Learning (PBL) model assisted by card media made the learning process more meaningful because students gained direct experience in preparing interview questions, conducting interviews, and writing interview texts systematically. The Problem Based Learning (PBL) model assisted by card media can be used as an alternative Indonesian language learning model to improve elementary school students’ writing skills.